Japanese Banks and the Asset Price "Bubble" - Fries, Steven (IMF Working Papers; Working Paper ;, 1993)
With the recent collapse of the asset price 'bubble,' Japanese banks encountered significant pressure from both a sharp decline in the value of equity holdings and a marked increase in bad loans. In August 1992, the Government initiated measures that stabilized equity prices and assisted banks in managing their nonperforming loans. While the major banks disclosed that 4.6 percent of their total loans were nonperforming at the end of FY 1992, a mechanical estimate of all banks' nonperforming and restructured loans is 6-7 percent of their total loans--a serious yet manageable problem. The main policy implications are to ensure the reasonably prompt resolution of the bad loan problem and to enhance market discipline to prevent its recurrence.